Diversity of Avifauna in Musiri Taluk, Tiruchirappalli District, Tamil Nadu, India - Muthusamy, A.; Siva, T.; Neelanarayanan, P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The present study investigates the avifaunal diversity of a part of Musiri Taluk, documenting a total of 120 bird species across 21 orders and 56 families. The order Passeriformes emerged as the most species-rich, comprising 26 families, followed by Charadriiformes with five families. Other notable orders include Coraciiformes (three families) and Accipitriformes, Strigiformes, Pelecaniformes, and Piciformes, each consisting of two families. Another fourteen orders each represented a single family. Based on the IUCN Red List, out of the 120 species recorded, 118 species were classified as Least Concern, while two species viz., the Red-necked Falcon (Falco chicquera) and the Pallid Harrier (Circus macrourus), were categorized as Near Threatened. Among the species, 77% were resident, and 23% were migratory, with key migratory species including the Pallid Harrier and Alpine Swift (Tachybaptus melba). The study further categorized the bird species based on their feeding habits as insectivores (36.60%), followed by omnivores (24.20%) and carnivores (22.50%). Other feeding types included granivores (11.70%), nectivores (2.50%), and frugivores (1.70%), with only a single piscivorous species, the Little Cormorant (Microcarbo niger), accounting for 0.80% of the total species. In line with the Wildlife Protection Act, 1972, 15 species were listed under Schedule I, and 103 species under Schedule II. Notably, the Rock Pigeon (Columba livia) and House Crow (Corvus splendens) are excluded from the Act. This study provides valuable insights into the avian diversity, distribution, and feeding behaviours in the region, offering important information for future conservation efforts.